Trading Volume, Dividend Payout Ratio, and Firm Size Against Stock Price Volatility in Companies Listed in the LQ45 Index: Volume Perdagangan, Devidend Payout Ratio, dan Firm Size Terhadap Volatilitas Harga Saham pada Perusahaan yang Terdaftar dalam Indeks LQ45 - Lailiya, Friska Nur; Hariasih, Misti (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study is to out wheter several factors such as Trading Volume, Dividend Pyout Ratio, and Firm Size to Stock Price Volatility. The sample in this study is companies listed on the LQ45 Index on the Indonesia Stock Exchange (IDX) in 2017 – 2021 totaling 19 compinies that have passed with the criteria for researchers. In this study using multiple regression analysis techniques or panel data and tested the hypothesis with a partial t test, a simultaneous F test with a significant level of 0,05 (5%) and a Coefficient of Determination Test (R2). The results of the study explain partially if the variable Trading Volume has a Positive and insignificant effect on Stock Price Volatility. The Variable Dividend Payout Ratio has a negative and insignificant effect on Stock Price Volatility. Firm Size variables have a negative and significant effect on Stock Price Volatility. Meanwhile, if simultaneously the Trading Volume, Dividend Payout Ratio, and Firm Size affect the Volatility of the Stock Price. The value of the Coefficient of Determination (R2) in this study was 0.621061 which means that the ability of free variables in explaining variations in bound variables was 62.1% while the remaining 37.1% was explained by other free variables outside the model.